Relationship between organizational culture, organizational innovativeness and organizational effectiveness in private universities in Iran - Ashraf, Giti (2013)
Empirical evidences indicate that if institutions of higher education are to survive and achieve long-run viability, they must be effective. Organizational culture and organizational innovativeness are viewed as important factors for improving the organizational effectiveness in these organizations. The aim of this study was to examine the correlations among organizational culture, organizational innovativeness and organizational effectiveness. Moreover,the mediating role of organizational innovativeness between organizational culture and organizational effectiveness was studied. The method used in the study was survey research. Based on the cluster sampling method, all full time faculty members from five branches of Islamic Azad University (lAU), located in Region one, Pars Province, Iran, were included in the sample of the study. The number of respondents was 369 participants. For measuring organizational culture, the Organizational Culture Assessment Instrument (OCAI) prepared by Cameron and Quinn (2006) was employed. Two new questionnaires were also developed for measuring organizational innovativeness and organizational effectiveness. The findings indicated that the mean scores for the three organizational culture types of clan, market and adhocracy were all moderate. However, the mean score for hierarchy culture was low. The mean scores for organizational innovativenessand organizational effectiveness were also moderate. Furthermore, the adhocracy culture, market culture and clan culture were found to have significant positive correlations with organizational innovativeness and organizational effectiveness. However, hierarchy culture showed no significant relationship with either organizational innovativeness or organizational effectiveness. Additionally, organizational innovativeness was found to have a significant positive relationship with organizational effectiveness. The results indicated that organizational innovativeness partially mediated the relationships among clan, adhocracy and market cultures with organizational effectiveness. Adhocracy culture contributed to predicting organizational effectiveness positively significantly. Clan, adhocracy and market cultures were positive and significant predictors for organizational innovativeness. Both technical and administrative innovations predicted organizational effectiveness positively significantly. The findings of this study demonstrated that adhocracy culture type is the positive predictor for organizational innovativeness and organizational effectiveness. Therefore,adhocracy culture needs to be strengthened within IAU in Iran in order to enhance the innovativeness and effectiveness of universities.